Improprieties politics and sexuality in Northern Irish poetry - Wills, Clair (Clarendon Press, 1993)
"Improprieties is an innovative and accessible study of contemporary Northern Irish poetry in the light of current debates about post-modernism, poetry and politics, and the figure of woman in Irish political discourse. Close readings of the work of Tom Paulin, Medbh McGuckian, and Paul Muldoon focus on the 'improper' elements of the poetry: the refusal of a sense of home, the disruption of 'traditional' poetic form, and the sexual narratives told." "The intersections between post-modern literary form and post-coloniality are currently an issue of intense concern, but they have rarely been addressed in the context of Irish culture. Clair Wills explores Northern Irish poetry in the light of the complex relationship between an 'international' poetic form and its national context. She assesses the relation between poetry and politics in Ireland; the limits of the 'Enlightenment' and 'Romantic' influences on Irish culture; the nature of political violence; femininity in Irish political discourse; and the division between public and private spheres of activity. These discussions culminate in extended analyses of the work of Paulin, McGuckian, and Muldoon, showing that their work cannot be understood without a redefinition of the relationship between poetry and politics." "Improprieties is a much-needed evaluation of Northern Irish poetry, distinguished by its theoretical sophistication and lucid critical readings of three notoriously complex but hugely important poets."--BOOK JACKET.